APPLICATION OF GAHARU-C FORMULATION (ORGANIC AND INORGANIC) FERTILIZER ON AGARWOOD PLANT AT SPECIFIC LOCATION IN TABANAN REGENCY - I Made Mega; A.A. Nyoman Supadma (International Journal of Biosciences and Biotechnology, 2019)
This study aim is to determine the effect of the application of Gaharu-C fertilizer formulation of sapwood formed on agarwood plants at three specific locations in Tabanan Regency. This research is a factorial experiment with basic CRD design (completely randomized design). The first factor is location specific consisting of 3 location namely: Pupuan Subdistrict (Pu), Penebel Subdistrict (Pnl), and District of East Selemadeg (Sl). The second factor was the treatment of the Gaharu-C formula fertilizer consisting of 2 ie: 0 (without fertilizer), and C (Gaharu-C fertilizer formulation: 100 g urea + 100 g SP-36 + 100 g KCl) + (7.5 kg compost ) + (75 g dolomite) per tree), each treatment replicated three times. Number of plants used as many as 18 trees. Parameters observed included increased stem diameter, sapwood color, weight of sapwood, resin content and soil chemical properties data. Data analysis used variance analysis and LCD test (?= 0.05). The results showed that specific-location factors had significant effect on increasing stem diameter. However, had no significant effect on the color of sapwood, sapwood weight and resin level of sapwood. The fertilizer factor of Gaharu-C formula has no significant effect on all parameters observed. The highest increase of stem diameter was obtained at Pupuan location (0.40 cm), followed by East Selemadeg (0.32 cm), and the lowest Penebel (0.15 cm). The weight of sapwood and the highest resin content was obtained at the Sl C treatment of 5.34 g and 6.43%. The best application of Gaharu-C fertilizer formulation is in East Selemadeg Subdistrict.